Nationalism and ethnic conflict in Indonesia - Bertrand, Jacques 1965- (Cambridge University Press, 2004)
Since 1998, which marked the end of the thirty-three-year New Order regime under President Suharto, there has been a dramatic increase in ethnic conflict and violence in Indonesia. In his innovative and persuasive account, Jacques Bertrand argues that conflicts in Maluku, Kalimantan, Aceh, Papua, and East Timur were a result of the New Order's narrow and constraining reinterpretation of Indonesia's 'national model'. The author shows how, at the end of the 1990s, this national model came under intense pressure at the prospect of institutional transformation, a reconfiguration of ethnic relations, and an increase in the role of Islam in Indonesia's political institutions. It was within the context of these challenges, that the very definition of the Indonesian nation and what it meant to be Indonesian came under scrutiny. The book sheds light on the roots of religious and ethnic conflict at a turning point in Indonesia's history
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1955-2002; Nationalismus; Politik; Nationalism / Indonesia; Ethnic conflict / Indonesia; Islam and politics / Indonesia; Gewalttätigkeit; Minderheitenfrage; Ethnizität; Islam; Religiöser Konflikt; Indonesia / Politics and government / 1998-; Indonesia / Ethnic relations; Indonesien